The first 60 days: chronicle of the oil spill at La Pampilla Refinery on the Peruvian coastline - Pulido-Capurro, Víctor (2022)
Objective. To make a first approximation of the environmental damage caused between January 15 and March 15 by the oil spill at the La Pampilla Refinery on the coast of the Peruvian marine littoral. Method. The research is based on documentary analysis and its orientation is empirical, exploratory, linked to real phenomena and predictive. It covered the period between January 15 and March 15, 2022. Primary sources were used and the search for information focused on three relevant aspects: the detailed description of the facts, the causes and effects of the spill and the reaction of the institutions responsible for safeguarding the conservation of the Peruvian sea and its biodiversity. Results. On January 15, 2022, at 17:18 hours, an oil spill occurred in the marine littoral zone of La Pampilla Refinery. The oil landing operations were in charge of the Spanish petrochemical multinational Repsol and several factors indicate that this company was negligent; even a high degree of corrosion was discovered in the oil transport pipes. MINAM confirms that there were 11 900 barrels. The spill had harmful consequences for the biodiversity of this area and many species probably reached their minimum population limits. Conclusion. The responsibility for the seriousness of the environmental disaster caused by the oil spill, on January 15, points directly to the Repsol company. The governmental reaction to the seriousness of the environmental damage was late. Sixty days after the spill, it is estimated that more than 500 marine species were affected.